Wearable, Healable, and Adhesive Epidermal Sensors Assembled from Mussel‐Inspired Conductive Hybrid Hydrogel Framework - Liao, Meihong; Wan, Pengbo; Wen, Jiangru; Gong, Min; Wu, Xiaoxuan; Wang, Yonggang; Shi, Rui; Zhang, Liqun (Advanced functional materials, 2017)
Healable, adhesive, wearable, and soft human‐motion sensors for ultrasensitive human–machine interaction and healthcare monitoring are successfully assembled from conductive and human‐friendly hybrid hydrogels with reliable self‐healing capability and robust self‐adhesiveness. The conductive, healable, and self‐adhesive hybrid network hydrogels are prepared from the delicate conformal coating of conductive functionalized single‐wall carbon nanotube (FSWCNT) networks by dynamic supramolecular cross‐linking among FSWCNT, biocompatible polyvinyl alcohol, and polydopamine. They exhibit fast self‐healing ability (within 2 s), high self‐healing efficiency (99%), and robust adhesiveness, and can be assembled as healable, adhesive, and soft human‐motion sensors with tunable conducting channels of pores for ions and framework for electrons for real time and accurate detection of both large‐scale and tiny human activities (including bending and relaxing of fingers, walking, chewing, and pulse). Furthermore, the soft human‐motion sensors can be enabled to wirelessly monitor the human activities by coupling to a wireless transmitter. Additionally, the in vitro cytotoxicity results suggest that the hydrogels show no cytotoxicity and can facilitate cell attachment and proliferation. Thus, the healable, adhesive, wearable, and soft human‐motion sensors have promising potential in various wearable, wireless, and soft electronics for human–machine interfaces, human activity monitoring, personal healthcare diagnosis, and therapy. Flexible, wearable, healable, and adhesive soft strain sensors are successfully developed from a conductive and biocompatible hybrid hydrogel framework for ultrasensitive human–machine interaction and healthcare monitoring. They exhibit fast self‐healing ability (within 2 s), highly self‐healing efficiency (99%), robust self‐adhesiveness, and a tunable conducting framework for real‐time, wireless, and accurate detection in human–machine interfaces, human activity monitoring, personal healthcare diagnosis, and therapy.